2018
DOI: 10.1002/bdd.2163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal ischemia on urinary excretion of lithium in rats

Abstract: Lithium, administered to patients with bipolar disorders, is mainly excreted in the urine, and tubular reabsorption is involved. This study characterized the renal excretion of lithium in rats subjected to renal ischemia for 60 min or 90 min. After intravenous injection of lithium chloride at 25 mg/kg, the pharmacokinetic parameters of lithium were determined. In sham‐operated rats, the renal clearance of lithium was calculated to be 1.49 ml/min/kg, and its ratio to creatinine clearance (fractional excretion) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…The plasma concentrations of lithium were in the therapeutic range (Table 2). The renal clearance and the fractional excretion of lithium of the control group (Table 2) were comparable to our previous values that were obtained from the experiments with the lithium injection as a bolus [15,16]. Fanconi syndrome decreased the renal clearance of lithium, and no effect on the fractional excretion of lithium was recognized (Table 2).…”
Section: Discussion/conclusionsupporting
confidence: 85%
See 2 more Smart Citations
“…The plasma concentrations of lithium were in the therapeutic range (Table 2). The renal clearance and the fractional excretion of lithium of the control group (Table 2) were comparable to our previous values that were obtained from the experiments with the lithium injection as a bolus [15,16]. Fanconi syndrome decreased the renal clearance of lithium, and no effect on the fractional excretion of lithium was recognized (Table 2).…”
Section: Discussion/conclusionsupporting
confidence: 85%
“…In the previous and the present studies, we showed that the renal clearance of lithium was decreased by S-flurbiprofen, renal ischemia, and Fanconi syndrome in rats [15,16]. And, S-flurbiprofen decreased the fractional excretion of lithium, and no effect of renal ischemia and Fanconi syndrome on the ratio was recognized [15,16]. Our animal studies indicate the heterogeneity in the effects of renal failures on the renal handling of lithium, suggesting that it is significant to examine effect of each renal failure on the lithium reabsorption as well as glomerular filtration.…”
Section: Discussion/conclusionsupporting
confidence: 57%
See 1 more Smart Citation
“…Lithium salts serve as mood-stabilizing and psychotropic agents (Dangana et al, 2019;Hart et al, 2020;Menshanov et al, 2016;Vosahlikova et al, 2020;Zhang et al, 2021) in patients with bipolar disorders (BDs) (Gehrmann et al, 2021;Luu & Rodway, 2018;Sung et al, 2019;Uwai et al, 2018), mania (Manto, 2012) and chronic depression (Medi c et al, 2020;Zhang et al, 2021). Lithium salts are also found in groundwater and drinking water, as recorded in the USA (Lindsey et al, 2021) and China (Shanghai) (Shen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lithium salts are psychotropic mood-stabilizing agents (Dangana, Michael, Omolekulo, Areola, & Olatunji, 2019;Hart, Perlis, & McCoy, 2020;Menshanov, Bannova, & Dygalo, 2016;Zhang, He, Yang, Li, & Cai, 2019) used for treating bipolar disorders (Luu & Rodway, 2018;Sung et al, 2019;Uwai, Suzuki, Kondo, Kawasaki, & Nabekura, 2018). Lithium salts are found in some natural mineral water (Dawson, 1991), vegetables and grains (0.5-3.4 mg/kg), meat (0.012 mg/kg) and dairy products (0.5 mg/kg) (Laurie Mischley, 2014).…”
Section: Introductionmentioning
confidence: 99%